Micellar Effects in the Reaction of Acid Violet-49 with Hydroxide Ion: Influence of Salts and Organic Solvents - Guard, H.Z.; Kothwala, D.M.; Joshi, H.M.; Nagar, T.N. (Asian Journal of Chemistry, 2010)
Cationic micelles of cetyl trimethylammonium bromide (CTAB) are known to increase the rate of reaction of triphenylmethyl carbonium ions with the hydroxide ion whereas the anionic micelles of sodium dodecyl sulphate (SDS) inhibit this rate. The addition of monohydric alcohols, viz., methanol, ethanol, n-propanol, n-butanol and solvents like acetone decrease the cationic micellar catalysed rate of carbinol fonnation while on the other hand increase the anionic micellar inhibited rate. The influence of electrolytes in the presence of CTAB has also been analysed.